Family Economics Writ Large - Jeremy Greenwood; Nezih Guner; Guillaume Vandenbroucke (Institute for the Study of Labor (IZA), 2016)
Powerful currents have reshaped the structure of families over the last century. There has been (i) a dramatic drop in fertility and greater parental investment in children; (ii) a rise in married female labor-force participation; (iii) a decline in marriage and a rise in divorce; (iv) a higher degree of assortative mating; (v) more children living with a single mother; (vi) shifts in social norms governing premarital sex and married women's roles in the labor market. Macroeconomic models explaining these aggregate trends are surveyed. The relentless flow of technological progress and its role in shaping family life are stressed.
Keywords: D1; E2; J1; O1; O4; Z1; 330; assortative mating; baby boom; baby bust; family economics; female labor supply; fertility; household income inequality; household production; human capital; macroeconomics; marriage and divorce; quality-quantity trade off; premarital sex; quantitative theory; single mothers; social change; survey paper; technological progress; women's rights